From Quiet to Vibrant: The Role of the Majelis Taklim Syiar Islam (MTSI) in Revitalizing Mosque Prosperity (A Case Study at PTPN IV Bah Jambi, Simalungun Regency) - Riqotul Qolbih Mukminin; Muhammad Habibi Siregar, (Institut Agama Islam Negeri (IAIN) Curup, 2026)
ABSTRACT Purpose − This study aims to analyze the work programs of the Majelis Taklim Syiar Islam (MTSI) of PTPN IV, Bah Jambi Plantation Unit and Palm Oil Mill Commissariat, Regional II, Simalungun Regency, in prospering the mosque, as well as to identify the supporting and inhibiting factors in its implementation. This research is important because MTSI is an Islamic da’wah institution operating within a corporate environment and possesses characteristics different from general majelis taklim, yet plays a strategic role in fostering the religious development of employees and surrounding communities. The research informants consisted of MTSI administrators as well as active congregants and community members involved in mosque activities. Method − This study employed a descriptive qualitative approach through field research methods, including in-depth interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using triangulation techniques. Findings − The results indicate that MTSI work programs oriented toward mosque empowerment include Qur’anic learning development, tahfiz and tilawah activities, muallaf guidance, Islamic holiday commemorations, and improvement of mosque facilities and infrastructure, which contribute to increased worship activities and congregational participation. This study recommends strengthening participatory and collaborative da’wah strategies to ensure that MTSI programs can be implemented more optimally and sustainably.